Enhancing Cognitive Learning Outcomes through STEM-Based Instruction: Evidence from High School Reaction Rate Learning - Dewi, Ucia Mahya; Muliaman, Agus (Electronic Journal of Education, Social Economics and Technology, 2026)
This study examined the effect of the STEM learning model on improving students’ cognitive learning outcomes in reaction rate topics using a quantitative experimental approach with a non-equivalent control group design. Two pre-existing classes were assigned as the experimental group (STEM) and the control group (Direct Instruction), both of which were given pretest and posttest assessments. The sample consisted of 70 Grade 11 students selected through purposive sampling, with 35 students in each group. The instrument used was a cognitive learning outcomes test measuring content, context, and cognitive competencies. Data were analyzed using descriptive statistics, normality testing, and the Mann–Whitney U Test at a significance level of 0.05. The results showed that the STEM group achieved a higher mean N-gain score (0.63) compared to the control group (0.38), with a statistically significant difference (p 0.05). These findings indicate that the STEM learning model has a positive and significant effect on improving students’ cognitive learning outcomes in reaction rate topics.